Feasibility and acceptability outcomes of the InMe trial - a randomised controlled trial in participants with subclinical eating and somatic symptom disorders - Marina Bobou; Michal Tanzer; Alkistis Saramandi; Caroline Selai; Aikaterini Fotopoulou (PLoS ONE, 2026)
Dysregulations in interoception have been associated with mental health disorders including eating and somatic symptom disorders. The present study addresses the feasibility and acceptability of a novel, behavioural intervention (InMe) in a healthy sample with low, self-reported interoception. The efficacy of the InMe intervention against an active control arm was tested in a randomised controlled trial (RCT) reported elsewhere, while the feasibility and acceptability of InMe were assessed in parallel and are fully reported here. Participants were randomly assigned to the intervention arm (InMe) or active control arm and stratified according to their self-reported gender and a cut-off score from the Eating Disorders Questionnaire (EDE-Q). Feasibility and accessibility measures included self-report scales and questionnaires, assessor checklists and ratings, as well as behavioural and physiological responses. Data was gathered from a total of 102 participants and encompassed trial recruitment and retention rates, the suitability of measurement tools, as well as the feasibility and acceptability of stressors, interventions and other trial procedures. The study found satisfactory feasibility in recruitment procedures, trial measurement tools, and intervention procedures. Participants perceived the intervention as acceptable, though minor adjustments for trial optimisation were identified. Overall, this feasibility study provided promising evidence regarding the acceptability and feasibility of an interoception based intervention in a RCT context. These findings offer valuable insights particularly for the design of future clinical trials for testing the efficacy of this intervention further in clinical populations.